Biochemical biomarkers of sublethal effects in Rhinella arenarum late gastrula exposed to the organophosphate chlorpyrifos - Sotomayor, Veronica (2015)
We determined the biochemical and molecular effects of the organophosphate insecticide chlorpyrifos (CPF) in the late gastrula embryonic stage of the South American toad Rhinella arenarum continuously exposed from fertilization (24 h). Our objective was to evaluate these responses as potential biomarkers at low, sublethal levels of the toxicant. We first established the EC50 for embryo arrest in 21.3 mg/L, with a LOEC of 16 mg/L. At 4 mg/L CPF, some embryos were unable to complete the dorsal lip of the blastopore and the yolk plug became blur, probably because of abnormal cell migration. Acetylcholinesterase activity, the specific biomarker for organophosphates, was unaffected by any of the tested concentrations of CPF (2–14 mg/L). In turn, 2 mg/L CPF increased the reduced glutathione levels and inhibited glutathione-S-transferase activity, suggesting an oxidative stress and antioxidant response. Catalase was induced by CPF exposure at higher concentrations (8 and 14 mg/L). We also studied transcription factor c-Fos as a signaling event related to development in early embryogenesis. Analysis of nuclear c-Fos protein showed two bands, both enhanced in embryos exposed to 2 and 8 mg/L CPF. While nuclear Erk protein was practically unaffected, Mek protein levels were induced by the OP. Transcription factor c-Fos may be then linking oxidative stress with developmental alterations observed due to CPF exposure. These molecular and biochemical responses observed in R. arenarum gastrula at sublethal CPF exposures may replace non-responsive AChE as very early biomarkers in toad gastrula.